Diseño e implementación de un prototipo automatizado para el pelado de plátano verde en el emprendimiento de un negocio. - Haro Araujo, Walther Germán (2020)
The research purpose of this thesis is to design and implement an automated prototype for green banana peeling in the entrepreneurship of a business, in the Tungurahua Province, Píllaro Canton, La Matriz sector, whose purpose is reducing the time that normally it involved the process of removing the shell from the raw as manual way. for further processes, and that the final product in this case the chifles are delivered to the consumer in the shortest possible time. To design of the prototype was used a computer-aided software as INVENTOR, this software served to size and model each of the parts that compose the machine, as is the main structure, the housing, the cutting mechanism, the conveyor belt mechanism, and so on. Regarding to electrical and electronic part was designed in a software called FRITZING, and the programming was done in the ARDUINO software. For the construction of this automated prototype square pipe, axles and stainless steel plates all of these of the AISI 304 series were used, since their properties are suitable for handling and food production. In addition this type of steel has anti-corrosive properties preventing its oxidation and that the raw material can be contaminated. It was also taken into account that the prototype is ergonomic, so that the operator can handle it in a comfortable position for this reason its measurements are 750 x 600 x 800 mm. In addition, it is easy to handle as it has its respective operation and maintenance manual.